Profesor Lorenzo Mérola. Maestro de Cirugía 1880-1935 - de Chiara, Juan Carlos; Valls, Alberto; Sarroca, Carlos; Balboa, Oscar (Cirugía del Uruguay, 1981)
100 years ago, on February 29, I was born in Montevideo Lorenzo Mérola, who was later a distinguished Master of Surgery. 100 years ago, on February 29, Lorenzo Mérola was born in Montevideo, which was later a distinguished Master of Surgery. Tribute made at the Uruguayan Society of Surgery on July 23, 1980, commemorating the centenary of his birth. It includes: The aponeurosis of the armpit / Lorenzo Mérola Modified radical mastectomy. Mérola Operation / Alberto Valls, Carlos Sarroca Mérola thoracic-abdominal approach Chest - abdominal approach (commentary) / Oscar Balboa Gastroplasty with colon / Lorenzo Merola Transtentorial occipital approach to the pineal gland / Pedro Benedek